2017
DOI: 10.1007/s00402-017-2733-8
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of coronoid-first repair in terrible triad injuries of the elbow

Abstract: The coronoid-first surgical approach, using a suture-lasso fixation method, has technical benefits for us and showed good clinical success in our series. This is important with postero-medial rotatory instability being common in our series of TTIs. We emphasize not to miss a TTI in an apparently isolated low Mason class radial head fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…IN THEIR CADAVERIC STUDY, cage DJ., et al found that the average anterior capsule attachment to the ulna is 6.4 mm distal to the coronoid tip and speculated that rarely, type 1 fractures could involve capsular detachment [20]. However, we found that all capsules were injured and avulsed from their insertion an- for coronoid tip repair in terrible triads injury as they found good clinical and radiographic outcomes postoperatively [15]. They suggested that a universal posterior midline incision is beneficial in medially and laterally approaching the elbow.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…IN THEIR CADAVERIC STUDY, cage DJ., et al found that the average anterior capsule attachment to the ulna is 6.4 mm distal to the coronoid tip and speculated that rarely, type 1 fractures could involve capsular detachment [20]. However, we found that all capsules were injured and avulsed from their insertion an- for coronoid tip repair in terrible triads injury as they found good clinical and radiographic outcomes postoperatively [15]. They suggested that a universal posterior midline incision is beneficial in medially and laterally approaching the elbow.…”
Section: Discussionmentioning
confidence: 53%
“…given the limited space [15]. What aided in exposure in our cases is that the radial heads were excised as they needed replacement;…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…[5][6][7][8] Recent studies have analyzed results of standardized protocols for TTI. Giannicola et al 5 in a series of 26 patients and Zhang et al 20 analyzing 13 cases reported a mean MEPS of 95 and 85 and mean DASH of 8 and 21, respectively. Nonetheless, despite the satisfactory clinical outcomes reported by the authors, the mean follow-up of the first publication was 31 months and 27 months for the second study, failing to address the sustainability of the results at long-term follow-up.…”
Section: Discussionmentioning
confidence: 97%
“…Elbow dislocation associated with both radial head and coronoid fractures earned its eponym “terrible triad injury” (TTI) for decades because of the poor prognosis [ 1 ]. With the improvement of knowledge on elbow biomechanics and pathoanatomy, the current standard strategy appeared to have yielded more favorable outcomes [ 2 , 3 ]. However, challenges persist.…”
Section: Introductionmentioning
confidence: 99%